The effect of high intensity interval training to physical condition of pencak silat atlet - Sartono Sartono; Firman Adityatama (JUARA : Jurnal Olahraga, 2019)
Pencak silat is the general term who described the art of we might as well and martial arts. An athlete can cope with the pencak silat If can enjoy his sports activity. The purpose of this research is to investigating the effect of High Intensity Interval Training (HIIT) toward physical condition on Pencak Silat of Students Activity Unit of STKIP Muhammadiyah Kuningan. This research using experimental method. The population of this research was Pencak Silat of Students Activity Unit of STKIP Muhammadiyah Kuningan, as many as 30 athlete. This research produce drawing conclusions, i.e. training with High Intensity Interval Training (HIIT) effect toward physical condition on Pencak Silat of Students Activity Unit of STKIP Muhammadiyah Kuningan